HUBUNGAN TINGKAT PENDIDIKAN DENGAN MOTIVASI BERPRESTASI GURU DALAM MENGAJAR DI TK SE KECAMATAN BUKIT RAYA PEKANBARU - Tiara Sukma Dewi; Ria Novianti; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Absract: The purpose of this research is to know the relationship level of teacher education with achiement motivation teachers in teaching in TK Se of Bukit Raya Pekanbaru District. This type of research includes quantitative research with the type of correlation. This research uses correlational researcKh that intends to test two variables to determine whether there is a link between the independent variable (X) and the dependent variable (Y). This research consists of 2 variables namely the level of education (X) and motivation to achieve the teacher. A teacher in a sub-district of Bukit Raya Pekanbaru which was made a sample of research consisting of 28 senior high School people, 12 people in D2, 9 people from D3, 24 people from S1 and 1 person in S2. More than half of teachers (63%) Have an accomplished motivation that is in the category of ' high '. It means that PAUD educators have a high achievement motivation in teaching in the KINDERGARTEN district of Tenayan Raya Pekanbaru. The result of correlation with the use of Chi Square test, the value of Pearson Chi-Square was obtained at 70.87 with Sig. 0.000. The research proved that the hypothesis that there was a relationship level teacher education with an accomplished motivation in teaching in kindergarten subdistrict of Bukitraya Kota Pekanbaru.Key Words: education level, achievement level